Components and Guidelines Risk Management of Schools under the Foundation of the Church of Christ in Thailand - Kanlachanphiset, Orawan; Amuayrat, Sopha; Buranachart, Santi; Gunma, Namfon (Rajapark Journal, 2022)
The purposes of this research were 1) to study the compositions of risk management of schools under the Foundation of The Church of Christ in Thailand and 2) to examine the guidelines of risk management of schools under the Foundation of The Church of Christ in Thailand. The research was a mix-methods study. Regarding data collection, the quantitative data were collected from all populations (93 administrators from schools under the Foundation of The Church of Christ in Thailand) by using a questionnaire. The data were analyzed to find its frequency, percentage, mean, and standard deviation (SD). The qualitative data were collected by interviews with five key informants. The data were analyzed using content analysis techniques. The results found that the overall composition of schools under the foundation of the Church of the Christ in Thailand was at high levels. The four compositions. In terms of the risk management guidelines for schools under the foundation of the Church of the Christ in Thailand, there were four steps: 1) the risk management culture, 2) the risk management policy, 3) the risk management structure, and 4) the risk management process, which was divided into 5 steps: (1) communicating and consulting, (2) establishing the context, (3) assessing the risks, (4) treating the risks, and (5) monitoring and reviewing.